1989
DOI: 10.1007/bf02471664
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection by a left ventricular assist device during reperfusion following acute coronary occlusion

Abstract: To evaluate the effects of a left ventricular assist device (LVAD) during the reperfusion period following acute coronary occlusion, sixteen mongrel dog hearts were subjected to 1 hour's occlusion of the circumflex coronary artery and then reperfused for 6 hours. In seven control dogs (control group), the hearts were reperfused without any support. In nine LVAD dogs (LVAD group), however, the left ventricles were supported by the application of a pneumatic driven diaphragm-type pump for 5 hours and then reperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The hemodynamic data of our experiments during acute coronary artery occlusion and reperfusion are similar to the data published by other authors [24,25]. The MAP, SV, CO and CI decreased during constant coronary artery occlusion, while the peripheral vascular resistance increased.…”
Section: Correlation Between Hemodynamic Data and Plasma Histamine Lesupporting
confidence: 80%
“…The hemodynamic data of our experiments during acute coronary artery occlusion and reperfusion are similar to the data published by other authors [24,25]. The MAP, SV, CO and CI decreased during constant coronary artery occlusion, while the peripheral vascular resistance increased.…”
Section: Correlation Between Hemodynamic Data and Plasma Histamine Lesupporting
confidence: 80%
“…These 26 studies evaluated a total of 488 animals, including 265 subjects assisted with either surgical or percutaneous LVAD. Types of LVAD included trans-valvular pumps in 13 studies (Impella in nine studies [10,[16][17][18][19][20][21][22][23]; Hemopump in four studies [24][25][26][27]); LV-distal arterial bypass in four studies (2 LV-femoral artery [28,29]; 1 LV-carotid artery [30]; and 1 LV-descending aorta [31]), left atrial-femoral artery bypass in five studies [29,[32][33][34] (including one TandemHeart study [35]), left atrial-ascending aorta bypass in one study [36], and right atrial-femoral/subclavian artery bypass in six studies [17,32,37] (3 studies with LV vent [38][39][40]) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…This left ventricular unloading, hypothetically, might result in infarct size reduction and increased left ventricular recovery. Several experimental studies have provided positive evidence for this hypothesis (6)(7)(8)(9). Although the underlying physiology is not yet completely understood, several mechanisms could play a role.…”
Section: Rationale For Mechanical Cardiac Assistancementioning
confidence: 94%
“…The concept of reduction of myocardial workload and reduction of myocardial oxygen demand through unloading is already used pharmacologically (ACE inhibitors). Furthermore, several experimental studies showed improved myocardial salvage and reduction of infarct size with mechanical unloading (6)(7)(8)(9). Surgical LVAD therapy is too cumbersome and associated with too much morbidity to become a serious strategy in STEMI patients without CS with the single purpose of myocardial recovery.…”
Section: Acute Stemi Without Cardiogenic Shockmentioning
confidence: 98%